The Development of the Outsourced Facility Service Market in the EU - Redlein, Alexander; Stopajnik, Eva (Journal of Applied Business and Economics, 2024)
The Facility Service (FS) industry lacks comprehensive scientific reports due to its fragmented representation in the NACE industry classification system in the EU. This article addresses this gap by offering insights into the FS market's turnover, number of companies, and employees. The study examines the development of turnover, company count, and employee numbers in the outsourced FS sector in the EU and the five major European economies since 2008. The European norm EN 15221:4 defines FS activities, which were cross-referenced with Eurostat's economic data to identify relevant FS services. Extensive data quality checks were conducted to ensure accuracy. From 2008 to 2018, the FS sector's size in terms of turnover and companies was estimated and compared across countries. Findings reveal that the EU's FS sector reached a turnover of over 1142 billion in 2017, with nearly 2 million companies and over 15 million employees. Despite the 2008/2009 financial crisis, the FS sector in the EU demonstrated stability compared to the broader economy in the selected countries.